Perbaikan Kualitas Pakan Ayam Broiler melalui Fermentasi Dua Tahap Menggunakan Trichoderma reseei dan Saccaromyces cerevisiae - Ibnu Hari Sulistyawan (Jurnal Agripet, 2015)
(Feedstuff Quality Improvement of Broiler Chicken with Two-Steps Fermentation by Trichoderma reseei and Saccaromyces cerevisiae)ABSTRAK. The aim of this study was to improve the quality of animal feedstuff from agriculture waste product i.e. corn cob, tapioca solid waste and soy bean pulp by two-steps fermentation using Trichoderma reseei as cellulotlytic microorganisms and yeast Saccaromyces cerevisiae as protein source. This fermented product the was used in broiler chicken in vivo test. A Completely Randomized Design with four treatments: R0(100% basal feed/BF); R1(100% BF+10% fermented corn cob); R2 (100% BF+10% fermented tapioca solid waste); R3(100% BF+10% fermented soy bean pulp). Each treatments were replicated for 5 times. The variables response tested were quality of feedstuffs before and after fermentation of protein, NDF and ADF digestibilities on broiler chicken in vivo test. The result indicated that the protein content after fermentation has increased but reduced in NDF and ADF fiber. Two steps fermentation had not improved significantly to protein digestibility (P0.05), but basic ration with fermented soybean pulp significantly improved (P0.01) on protein digestibility.